2021
DOI: 10.1111/1755-0998.13318
|View full text |Cite
|
Sign up to set email alerts
|

Long read sequencing of Toona sinensis (A. Juss) Roem: A chromosome‐level reference genome for the family Meliaceae

Abstract: Chinese mahogany (Toona sinensis) is a woody plant that is widely cultivated in China and Malaysia. Toona sinensis is important economically, including as a nutritious food source, as material for traditional Chinese medicine and as a high‐quality hardwood. However, the absence of a reference genome has hindered in‐depth molecular and evolutionary studies of this plant. In this study, we report a high‐quality T. sinensis genome assembly, with scaffolds anchored to 28 chromosomes and a total assembled length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 59 publications
7
23
2
Order By: Relevance
“…TPS-a and -b subfamilies were the main subfamilies in A. indica , approximately 37.5 and 32.5% of the total AziTPS genes in phylogenetic analysis. This is in accordance with other plant species, including tea, grape, and Chinese mahogany ( Chen et al, 2011 ; Zhou et al, 2020 ; Ji et al, 2021 ). Furthermore, we identified putative A. indica -specific TPSs using phylogenetic analysis and a cutoff of 55% identity, which indicates separate subfamily assignment ( Liu et al, 2018 ; Tu et al, 2020 ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…TPS-a and -b subfamilies were the main subfamilies in A. indica , approximately 37.5 and 32.5% of the total AziTPS genes in phylogenetic analysis. This is in accordance with other plant species, including tea, grape, and Chinese mahogany ( Chen et al, 2011 ; Zhou et al, 2020 ; Ji et al, 2021 ). Furthermore, we identified putative A. indica -specific TPSs using phylogenetic analysis and a cutoff of 55% identity, which indicates separate subfamily assignment ( Liu et al, 2018 ; Tu et al, 2020 ).…”
Section: Resultssupporting
confidence: 89%
“…This may also explain the fact that A. indica had more expanded gene families than C. sinensis . Our result is in agreement with the research of Chinese mahogany, which indicated that a recent WGD occurred in Toona sinensis ( Ji et al, 2021 ). The occurrence of recent WGD mixed with gene duplications has been reported in Papaver somniferum L. genome ( Guo et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A total of 126 genes, including 82 protein-coding genes, 36 tRNA genes, and eight rRNA genes, were identified [118]. Ji et al (2021) reported a high-quality T. sinensis genome assembly with scaffolds anchored to 28 chromosomes, an assembled length of 596 Mb, and a total of 34,345 genes predicted in the genome after homology-based and de novo annotation analyses [119].…”
Section: Omicsmentioning
confidence: 99%